Case studies continue to illuminate the cognitive neuroscience of memory. (May 2014) - Rosenbaum, R. Shayna; Gilboa, Asaf; Moscovitch, Morris
Abstract : The current ubiquity of functional neuroimaging studies, and the importance they have had in elucidating brain function, obscures the fact that much of what we know about brain–behavior relationships derives largely from the study of single‐ and multiple‐patient cases. A major goal of the present review is to describe how single cases continue to uniquely and critically contribute to cognitive neuroscience theory. With several recent examples from the literature, we demonstrate that single cases can both challenge accepted dogma and generate hypotheses and theories that steer the field in new directions. We discuss recent findings from case studies that specify critical functions of the hippocampus in episodic memory and recollection, and clarify its role in nonmnemonic abilities. Although we focus on the hippocampus, we discuss other regions and the occurrence of new associative learning, as well as the involvement of the ventromedial prefrontal and parietal cortices in memory encoding and retrieval. We also describe ways of dealing with the shortcomings of case studies, and emphasize the partnership of patient and neuroimaging methods in constraining neurocognitive models of memory.